STUDY OF SERUM VITAMIN D CONCENTRATIONS IN ELDERLY PATIENTS UNDERGOING PERIODIC HEMODIALYSIS AT FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Vitamin D deficiency has been shown to be highly prevalent in the elderly. In patients undergoing maintenance hemodialysis, this condition becomes even more severe.Objective: To evaluate serum vitamin D levels in elderly hemodialysis patients at Huu Nghi Hospital and identify associated factors.Subjects and Methods: A descriptive study was conducted on outpatients receiving maintenance hemodialysis at the Department of Nephrology – Dialysis, Huu Nghi Hospital from May 2025 to August 2025.Results: The study included 65 elderly hemodialysis patients, of whom 63.1% were male; the mean age was 76.21 ± 8.05 years. Most patients had a normal BMI (72.3%). The mean serum 25(OH)D level was 23.11 ± 12.54 ng/mL. The prevalence of vitamin D deficiency was high, with moderate deficiency being the most common (35.4%), followed by mild deficiency (27.7%) and severe deficiency (10.8%). There were no significant differences in 25(OH)D levels by sex, age group, or BMI (p > 0.05). In the multivariate regression analysis, serum albumin
Keywords: VitaminD, dialysis